Penolakan Waris Akibat Gugatan Hutang Piutang Pihak Ketiga Ditinjau Dari Burgerlijk Wetboek - Andyna Susiawati Achmad (Universitas Merdeka Madiun, 2022)
Abstract— Humans always have legal relations with other legal subjects. Legal relations begin when humans are born until die. The legal relations when a human die is known as an inheritance relationship, between the heir and all his heirs regarding the inheritance of the heir. Inheritance law in Indonesia is regulated in a plural manner, one of which is regulated in the Burgerlijk Wetboek. Burgerlijk Wetboek recognizes the existence of inheritance rejection mechanisms by heirs. Refusal of inheritance usually occurs when the total liabilities of the inheritance of the testator are greater than the assets. The problem is usually the heirs do not necessarily know for sure how much the net amount of the inheritance is when the testator dies. The method approach in this research is normative juridical with secondary data which is analyzed qualitatively. There is no clear and complete mechanism for the heirs to refuse the inheritance. This study examines the refusal of inheritance by the heirs when the heirs only learn about the liabilities left by the testator, after a lawsuit from a third party.